2022
DOI: 10.1111/and.14524
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between obesity‐related markers, biochemical metabolic parameters, hormonal profiles and sperm parameters among men attending an infertility clinic

Abstract: Obesity causes many health problems as well as has negative effects on fertility. However, little is known about the association between obesity‐related markers (hip circumference (HC), waist circumference (WC), waist to hip ratio (WHR), waist to height ratio (WHtR), body fat mass (BFM), skeletal muscle (SM), resting metabolism (RM), visceral fat (VF), and visceral adiposity index (VAI)) and sperm parameters. This cross‐sectional study was conducted on 98 men in three groups: normal‐weight (Nw; body mass index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(51 reference statements)
1
1
0
1
Order By: Relevance
“…They also reported that waist circumference (WC), waist-to-hip ratio (WHR), skeletal muscle (SM), and visceral fat (VF) did not affect the quality of sperm parameters. Their result was consistent with our study [ 39 ]. Bahar GUR et al also reported that higher VFT (visceral fat thickness) was negatively correlated with sperm normal morphology, but it did not affect sperm progressive motility and sperm concentration.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…They also reported that waist circumference (WC), waist-to-hip ratio (WHR), skeletal muscle (SM), and visceral fat (VF) did not affect the quality of sperm parameters. Their result was consistent with our study [ 39 ]. Bahar GUR et al also reported that higher VFT (visceral fat thickness) was negatively correlated with sperm normal morphology, but it did not affect sperm progressive motility and sperm concentration.…”
Section: Discussionsupporting
confidence: 94%
“…Several recent studies with interesting results have been conducted since the aforementioned meta-analyses [39][40][41][42]. For example, in a cross-sectional study, Esmaeili et al found that BMI was negatively correlated with normal sperm morphology, sperm total motility, and progressive motility, but it had no effect on sperm volume and concentration.…”
Section: Discussionmentioning
confidence: 99%
“…По данным ряда исследователей, уровень общего тестостерона в сыворотке крови и соотношение Т/Э значительно выше у бесплодных мужчин с нормальным индексом массы тела (ИМТ) по сравнению с бесплодными мужчинами, имевшими ожирение (р <0,001), хотя при этом оба показателя не всегда достоверно коррелировали с параметрами эякулята [49][50][51][52].…”
Section: диагностические аспекты обмена эстрогенов: значение соотноше...unclassified